The Influence of Learning Styles on Mathematical Performance among Junior High School Students - Nathaniel Autida, (Journal of Educational Issues, 2024)
Learning styles are different approaches individuals prefer for acquiring knowledge and information. This study examines the influence and relationship between learning styles and mathematical performance among junior high school students at Tolotolo National High School. By identifying and recognizing students’ preferred learning styles, educators can better understand and meet students’ learning needs. The research aims to identify the dominant learning style among students and its correlation with mathematical performance. Results show that students at Tolotolo National High School predominantly prefer auditory learning. However, the study found no significant correlation between auditory learning and mathematical performance. Interestingly, a significant relationship was found between kinesthetic learning styles and higher academic achievement in Mathematics with a significance score of 0.001. These findings suggest that while auditory learning is prevalent, kinesthetic learning plays a role in academic success. These insights contribute to developing effective teaching strategies and styles that encourage students to become more successful academically.